Stereoselective Synthesis of Highly Functionalized Aminobenzothiazole-Fused Spirooxindole Derivatives: in silico and in vitro Anti-Diabetic Studies - Nivetha, Narayanasamy; Patil, Shashank M.; Ramu, Ramith; Sreenivasa, Swamy; Velmathi, Sivan (Synthesis, 2023)
A series of highly functionalized spirooxindole pyrrolizidine/pyrrolothiazole derivatives have been synthesized by the three-component 1,3-dipolar cycloaddition reaction of benzothiazolyl amides with isatin-based azomethine ylides. The pharmacologically significant spirooxindole derivatives bearing one quaternary carbon and four stereocenters were obtained in excellent yields (up to 93%). The compounds were screened for their anti-diabetic activity against two enzymes, α-glucosidase and α-amylase. The results exhibited potent inhibitory activity against these enzymes, especially N-(benzo[d]thiazol-2-yl)-5-fluoro-2-oxo-7′-phenyl-1′,6′,7′,7a′-tetrahydro-3′H-spiro[indoline-3,5′-pyrrolo[1,2-c]thiazole]-6′-carboxamide (6b), which showed excellent activity compared to the standard acarbose. Molecular docking against the receptors showed excellent interactions of the synthesized compounds in a similar way to acarbose. Further, the docking results of the spirooxindole pyrrolothiazole (6b) evinced the strong binding interactions of the compound with the receptors. Additionally, molecular dynamics simulations were carried out and confirmed the stability of the spirooxindole pyrrolothiazole (6b) in the active pockets of enzymes over 100 ns.
Keywords: 2-aminobenzothaizole; 1,3-dipolar cycloaddition; spirooxindole; anti-diabetes